Analysis of Energy Conversion Law in Vehicle Collision Accident. Issue 7 (April 2020) - Chi, Hongpeng; Gong, Bing
Abstract: The characteristics of automobile collision are introduced. The dynamic analysis of automobile collision accident process is carried out. The whole collision process is reproduced. The energy conversion law of collision accident process is analyzed qualitatively and quantitatively. The calculation of collision deformation of experimental vehicle under three conditions is completed.